Religion In TheWorkplace: The Legal Framework In Portugal - Susana Sousa Machado (European Scientific Journal, ESJ, 2016)
This paper deals with a reflection around religion in the workplace, especially in the Portuguese context, from a legal perspective. Thus, the goal here is to identify the main focal points of the legal framework in Portugal. We intend to demonstrate the most significant aspects of protection but also the weaknesses of the system. This reflection goes about perfecting opportunities to the level of articulation between employers’ organization rights and religious freedom of the employees.